Pain management in rheumatic diseases - Styczyński, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2006)
There are two kinds of pain in rheumatic diseases: nociceptive and non nociceptive (neurophatic, psychogenic pain). Nociceptive pain is due to inflammatory process not only in rheumatoid arthritis and inflammatory spondyloarthropathy, but in osteoarthritis and intervertebral disc herniation as well. Damage of joint structure, compression, and destruction of intra- and roundarticular soft tissue are additional causes of pain. The pain associated with rheumatic disease is generally managed pharmacologically according to the WHO analgesic ladder, with complementary medication and kinesio-, balneo-, physiotherapy. In special cases rheumatologist, neurologist, neurosurgeon, orthopedist, psychiatrist should be involved in the process of pain management in rheumatic diseases.